ATTITUDES OF HEALTHCARE STUDENTS TOWARDS BREASTFEEDING AFTER THE FIRST YEAR OF CHILD'S AGE - Irena Hribar; Renata Vettorazzi (The Society for Children with Metabolic Disorders, 2023)
Introduction: The World Health Organisation recommends exclusive breastfeeding for the first six months of the child's age and then, with complementary feeding, breastfeeding until the child's second year, or longer if this suits the woman and the child. In the literature, women report pressure to stop breastfeeding by the first year of the child's life. In this study, we wanted to find out how healthcare students at the Faculty of Health Sciences at the University of Ljubljana feel about breastfeeding after the first year. Methods: We used a quantitative, non-experimental research method. The answers were obtained by means of a structured questionnaire on a sample of 250 students. For data analysis, descriptive statistics, Pearson's correlation coefficient, Welch's t-test and ANOVA test were used. Results: We found that students who have more knowledge have better acceptance of breastfeeding after the first year of age and have more positive feelings about breastfeeding. Of all the study fields, midwifery students have the most knowledge about breastfeeding, while there are no statistically significant differences between students of other study fields. Conclusion: To create optimal conditions for women who want to breastfeed for longer, it is necessary that health professionals have adequate knowledge about the benefits, barriers, recommendations and problems associated with breastfeeding after the first year of the child's age. These topics should be compulsorily included in undergraduate and postgraduate curricula.